The Impact of Education in South Asia 2018
DOI: 10.1007/978-3-319-96607-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Getting in, Dropping out, and Staying on: Determinants of Girls’ School Attendance in Nepal

Abstract: Ethnographic research was carried out in 1997-98 to identify factors that determined school attendance among Nepali women in the Kathmandu Valley a generation ago. Findings indicate that gender, caste, poverty, cultural prejudice, and rural residence prevented a majority from going to school. Of those who went, most, regardless of academic talent, were pulled out in order to work at home, as wage laborers and domestic servants, or to enter arranged marriages. Only a small minority made the decision to leave sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…Therefore, they conclude that traditional indicators of development had little impact on discriminatory educational outcomes. LeVine's (2006) ethnographic study of Nepal examines the determinants of school attendance of girls and the reasons behind their dropping out of school. The study finds that since the 1990s, profound socioeconomic transformations have led to a more equitable attitude of parents toward their children's education, although girls were still less likely to complete their education or attain higher education because of marriage.…”
Section: Motivationmentioning
confidence: 99%
“…Therefore, they conclude that traditional indicators of development had little impact on discriminatory educational outcomes. LeVine's (2006) ethnographic study of Nepal examines the determinants of school attendance of girls and the reasons behind their dropping out of school. The study finds that since the 1990s, profound socioeconomic transformations have led to a more equitable attitude of parents toward their children's education, although girls were still less likely to complete their education or attain higher education because of marriage.…”
Section: Motivationmentioning
confidence: 99%
“…While these findings may suggest a limited influence of household and the community factors, girls from the upper caste/ ethnic group, however, had higher odds of aspiring to study beyond class 12. This association mattered more for older girls, and relates to the fact that while secondary school enrolment is now the norm in Nepal, the most disadvantaged girls still face barriers to education [73]. This finding stresses the importance for programs to prioritizing girls from socially-excluded groups vis-a-vis education investments, as well as understanding and addressing socio-cultural barriers that hinder girls from lower caste/ethnic groups to aspire to higher education.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the study carried out by Cunningham et al (27) which showed that the educational level in Nepal has substantially progressed during recent decades because the net enrolment rate in elementary education has increased from 66.3% in 1999 to 97% in 2016. Likewise, female participation in educational attainment has also increased dramatically (28) . This phenomenon can be observed globally as the role of women has changed over the last decades (29) .…”
Section: Discussionmentioning
confidence: 99%